Electrosynthesis of Cu / ZnO nanocomposite electrode on ITO electrode and its application in oxidation of ascorbic acid and glucose - Quayum, M Emran; Biswas, Bablu; Bhuiyan, Md Khairul Hassan (Journal of the Asiatic Society of Bangladesh, Science, 2014)
In the present study Cu nanoparticles (NPs), ZnO nanorods have been deposited on indium tin oxide (ITO) electrode and thereby Cu-NPs /ZnO / ITO composite film electrode has been prepared. The prepared nanostructures have been characterized by using scanning electron microscope (SEM). The shape of the electrochemically deposited ZnO follow rod like structure on ITO electrode, CuNPs follow irregular spherical shape when electrodeposited on ITO electrode. Oxidation of ascorbic acid on bare ITO electrode is favorable than that of ZnO modified ITO electrode but Cu-NPs/ ZnO composite electrode had high sensitivity and stability and showed higher catalytic current for glucose oxidation. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17855 J. Asiat. Soc. Bangladesh, Sci. 39(2): 183-190, December 2013